2016
DOI: 10.15740/has/ijppht/7.2/228-236
|View full text |Cite
|
Sign up to set email alerts
|

Effect of modified atmospheric packaging on shelf-life of Cham-cham

Abstract: The present study was carried out to evaluate the shelf-life of Cham-Cham using modified atmospheric packaging (MAP). Cham-Cham stored under refrigeration temperature (7±2 0 C) in modified atmospheric condition showed significantly higher shelf-life than the Cham-Cham stored at same temperature in normal packaging condition. The compositional attributes such as fat, protein, total carbohydrate and ash of Cham-Cham increased significantly where as moisture was significantly decreased up on storage at 7±2 0 C. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…It can be characterized as an individual perception of sweetness, which remained unaffected during the storage. The observations made in the current research are in accordance with the findings reported for several other products, for example, brown peda (Londhe et al, 2012), danedar khoa (Sharma et al, 2001) and cham-cham samples (Sindhav et al, 2016) during storage under MAP. Also, a similar trend was recorded on stored kalakand by Jain et al (2015) and stored lal peda by Jha et al (2015).…”
Section: Hedonic Characterizationsupporting
confidence: 92%
“…It can be characterized as an individual perception of sweetness, which remained unaffected during the storage. The observations made in the current research are in accordance with the findings reported for several other products, for example, brown peda (Londhe et al, 2012), danedar khoa (Sharma et al, 2001) and cham-cham samples (Sindhav et al, 2016) during storage under MAP. Also, a similar trend was recorded on stored kalakand by Jain et al (2015) and stored lal peda by Jha et al (2015).…”
Section: Hedonic Characterizationsupporting
confidence: 92%